Assessing Social Capital: Small and Medium Sized Enterprises in Germany and the U.K - Spence, Laura J. (Journal of business ethics, 2003)
"Social capital" can be considered to be the product of co-operationbetween various institutions, networks and business partners. It haspotential as a useful tool for business ethics. In this article weidentify categories pertinent to the measurement of social capital insmall and medium sized enterprises (SMEs). By drawing on three differentsectors, one business-to-business service, one business-to-customerservice, and one manufacturing, we have enabled the consideration ofsectoral differences. We find sector to play an important part inrelation to business practices and social capital. Our inclusion of SMEsfrom Germany and the United Kingdom has called attention to cultural,institutional and economic aspects of two regions of Europe and how theycan influence SME social capital. Social capital is found to beinfluenced by context and, in particular, institutional arrangements. Inanalysing the data we note particular areas of interest from the pointof view of SMEs and social capital as being: formal engagement,networking within sectors, networking across sectors, volunteerism andgiving to charity, and finally a focus on why people engage. We concludethat there is a considerable amount of further research needed on socialcapital, SME's and business ethics.